Levantamento detalhado das áreas de produção de algodão em Mato Grosso : fatores edafoclimáticos e sua relação com a produtividade - Santos, Aline dos (2018)
The area under cotton cultivation has considerably increased in the state of Mato Grosso. In this context, it is important to improve knowledge about the main cotton management systems as well as the characteristic of these production areas. The objective of this study was to identify the main limiting factors to cotton productivity as well as soil indicators of adequate management production. In the crop seasons of 2011/2012 and 2012/2013, a total of 1,162 plots (263 farms) were sampled in the municipalities of Mato Grosso: Primavera do Leste, Campo Verde, Rondonópolis, Campo Novo de Parecis, Sapezal, Lucas do Rio Verde and Sorriso, which were located in the Cerrado biome and Cerrado/Amazon ecotone. In each plot, soil samples were taken in the 0-20 cm layer to evaluate soil fertility, carbon and nitrogen stocks, texture and bulk density. At the time of harvesting, seed cotton yield was estimated after collection of 4 rows (5 m each). Using a dendrogram, six cotton production cluster were established. Clay contents varied from low to high values. Clusters with higher base saturation and pH values were comprised by areas under longterm cotton cultivation. The highest soil carbon and nitrogen stocks were observed in the groups that used conservation practices. The highest yields of cotton in the state of Mato Grosso were obtained in regions with higher altitudes, associated with the use of conservation practices.